EKSPLORASI FARITIA TERHADAP LINGKARAN - Karyenti Merintan Sani Lahagu; Hardi Tambunan; Ruth Mayasari Simanjuntak (Universitas Nias Raya, 2025)
This study aims to explore the relationship between the traditional musical instrument Faritia from Nias and the concept of the circle in terms of its visual form, rhythmic structure, and social symbolic meaning. Faritia is a metal idiophone shaped like a circle, commonly used in traditional ceremonies such as Mamozi Aramba. The research approach is a literature review, collecting and analyzing various sources on organology theory, Euclidean rhythm, and ethnomusicological studies. The findings indicate that the physical form of Faritia reflects principles of acoustic resonance and symbolic values commonly found in traditional cultures: balance, wholeness, and continuity. The rhythmic patterns produced by Faritia show a tendency towards cyclical beat distribution similar to the concept of Euclidean rhythms. Moreover, in social practice, Faritia is played within circular formations that reinforce collective meaning and community unity. Thus, Faritia functions not only as a traditional musical instrument but also as a multidimensional cultural symbol representing the circle in the physical, musical, and social structures of Nias society.